Structural and functional analysis of the yeast general transcript elongation factor, TFIIS - Awrey, Donald E. (My University, 1997)
Transcription by GNA polymerases is regulated at several stages, including initiation, elongation, and termination. The rate of transcipt elongation can be reduced by a multitude of factors, two of which include the template DNA sequence and DNA binding proteins. DNA sequences can cause the elongating polymerase to become stalled. Stalled ternary complexes containing eukaryotic RNA polymerase II require the transcription factor TFIIS to stimulate the resumption of transcription. This stimulation involves the endonucleolytic cleavage and release of oligonucleotides from the 3' terminus of the nascent transcript, with subsequent progression through these modulatory sequences.
I have determined the domain structure of yeast TFIIS by limited proteolytic digestion and assigned functions to the domains required for TFIIS activities in vitro. Using a novel binding assay, the surfaces of both yeast RNA polymerase II and yeast TFIIS responsible for their association were determined. The region of yeast RNA polymerase II mediating the interaction with TFIIS was determined to include amino acid residues between 1208 and 1264, which is conserved among eukaryotic RNA polymerase II homologues. The region of TFIIS that interacts with RNA polymerase II was localized to the region 143 to 240 and subsequently to a cluster of amino acid residues contained within this domain. The carboxyl terminal domain of TFIIS is required for the stimulation of endonucleolytic activity by elongating RNA polymerase complexes. Based on the three dimensional structural of TFIIS, I have identified amino acid residues that are important for the stimulation of the nascent transcript cleavage activity. Several site-directed mutants of TFIIS were unable to stimulate the cleavage activity, yet maintained wild type binding characteristics. I propose a model that describes the mechanism of TFIIS stimulated release of RNA polymerase II from stalled ternary complexes.
Keywords: Biology; Biology